Liquid demixing in elastic networks: Cavitation, permeation, or size selection?. (1st March 2022) - Ronceray, Pierre; Mao, Sheng; Košmrlj, Andrej; Haataja, Mikko P.
Abstract: In cells, phase-separated liquid condensates interact mechanically with surrounding elastic networks such as chromatin and cytoskeleton. By considering the trade-offs between elastic, wetting, and interfacial energies, we theoretically show that three droplet phases can be thermodynamically stable: macroscopic droplets that either cavitate or permeate the network, and mesh-size–limited microdroplets. We show that network strain stiffening further enhances this latter size-limitation effect. Our theory predicts the possibility of yet-unobserved droplet phases in the cytoplasm and nucleoplasm.